PEMBELAJARAN KOOPERATIP TIPE TEAM GAMES TOURNAMENT (TGT) SEBAGAI UPAYA MEMPERBAIKI PERILAKU BELAJAR SISWA DALAM PEMBELAJARAN GEOGRAFI - Ika Yudaningsih; Pargito Pargito; Yarmaidi Yarmaidi (Jurnal Studi Sosial / Journal of Social Studies, 2013)
The purpose of this research is to improve students' learning behavior in learning geography with the type of cooperative learning teams-games-tournaments (TGT).This research is a classroom action research (CAR) conducted in SMA Negeri 2 Tumijajar Bone Western Onion collaborative and participatory. The subjects in this study were all students of class XI IPS 3 in SMAN 2 Tumijajar totaling 27 students. The object of this research is to improve students' learning behavior in learning geography with type TGT cooperative learning teams-games-tournaments, which consisted of the presentation of the class, group learning, games, tournament, and awards groups. Religious studies is a class XI IPS 3 SMAN 2 Tumijajar Margomulyo village, subdistrict Tumijajar Bone WesternOnion. The study was conducted in three cycles and each cycle consisted of three meetings.Results showed changes in students' learning behavior in learning geography by learning models kooperatis TGT type that has been pursued through the planning stages (planning),action (acting), observation (observing), and reflection (reflecting) and revision. Results showed that behavioral changes learned at each cycle. Changes in student learningbehavior, (1) attention, active learning, (2) independent in learning, (3) interacting in the classroom, (4) actively participate in learning activities, (5) a relevant answer to thequestion, (6) rapid response to environmental conditions.Keywords: cooperative learning type TGT, improving learning behavior, learning geography